A new legal treatment for psychopaths? Perplexities for legal thinkers. (September 2017) - Gonzalez-Tapia, Maria Isabel; Obsuth, Ingrid; Heeds, Rachel
Abstract: Public perception, fueled not only by popular and news media but also by expert claims that psychopaths are archetypes of evil: incorrigible, remorseless, cold-blooded criminals, whose crimes manifest in the most extreme levels of violence. But is there empirical evidence that psychopaths truly are what they are portrayed to be? If so, should the law respond, and adjust its treatment of psychopaths in court — permitting psychopathy to be admitted under an insanity defense and/or resulting in mitigation? In this paper, we demonstrate that fundamental questions from the law to science remain unanswered and must be addressed before any alternative treatment of psychopathy can be considered. As it stands, psychopaths cannot be reliably defined or diagnosed and, as we will demonstrate, even the presumed link with criminal dangerousness is problematic. We conclude that the current legal approach should not be modified, however, if preliminary findings regarding impairments in impulsivity/self-control are confirmed, some, but not all individuals who fall under one definition of psychopathy may merit different treatment in future.